Soil clays : linking geology, biology, agriculture, and the environment - Churchman, G. J.; Velde, Bruce (Boca Raton : CRC Press, 2019)
"This book aims to help improve predictions of important properties of soils through a modern understanding of their highly reactive clay minerals as they are formed and occur in soils worldwide. It examines how clays occur in soils and the role of soil clays in disparate applications"--
Includes bibliographical references and index.
Keywords: Clay